2019
DOI: 10.17583/ijep.2019.3356
|View full text |Cite
|
Sign up to set email alerts
|

Student Interest and Engagement in Middle School Physical Education: Examining the Role of Needs Supportive Teaching

Abstract: This study examines the complexities of the social learning environment in middle school physical education. Specifically, we investigate the independent and interactive predictive effects of situational interest and needs supportive teaching on students’ personal interest and class engagement. Middle school students (N = 388) in compulsory physical education courses completed questionnaires on situational interest, needs supportive teaching, personal interest, and behavioral and emotional engagement. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…The Decision of the Central Committee of the Communist Party of China on Some Major Issues of Comprehensively Deepening the Reform also emphasizes that physical education courses and physical exercises should be strengthened to promote the cultivation of students’ physical and mental health behaviors. Some scholars have found that physical exercise not only promotes the healthy development of students, but also plays an important role in cultivating students’ core qualities ( Otundo and Garn, 2019 ). Therefore, hypothesis 1 is proposed in this study: junior high school students’ physical exercise can positively predict school adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The Decision of the Central Committee of the Communist Party of China on Some Major Issues of Comprehensively Deepening the Reform also emphasizes that physical education courses and physical exercises should be strengthened to promote the cultivation of students’ physical and mental health behaviors. Some scholars have found that physical exercise not only promotes the healthy development of students, but also plays an important role in cultivating students’ core qualities ( Otundo and Garn, 2019 ). Therefore, hypothesis 1 is proposed in this study: junior high school students’ physical exercise can positively predict school adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…This condition presented that if students have an interest in something then students will tend to focus greater attention on something they like (Simbolon, 2014). Even if the teacher allows students to choose their physical activity according to their expectation will also make them survive to continue to engage in physical activity and connecting in-class activity to their life outside the classroom (Otundo & Garn, 2019).…”
Section: Internal Factorsmentioning
confidence: 99%
“…That was in line with the results of this research which revealed that activities factor was defined as the majority in the high classification. Specifically designed activities according to differences in skill levels each student will provide support for the expected mastery of competencies (Otundo & Garn, 2019). There is a positive feeling of the activity they follow as well as a great curiosity that will participate in developing students' initial interest in the activity (Hidi & Ann Renninger, 2006).…”
Section: Internal Factorsmentioning
confidence: 99%
“…Interest is always connected with the process that could contribute towards learning and academic achievement. Interest drives the students to elevate their desire to achieve their goals by being more aware of the learning environment needs [11]. As a result, students that tend to be interested in the STEM field will have a direct effect on the nation's growth.…”
Section: Introductionmentioning
confidence: 99%